A step towards the chronology of early medieval head ornaments in the Eastern Alps - Pleterski, Andrej (Arheološki vestnik, 2013)
The article proposes a classification system for early medieval head circlets in the Eastern Alps. The relative and absolute chronologies of these rings are established with the help of stratigraphic, topographical, and chronological analysis of selected cemeteries. Radiocarbon dating is tested and it appears that from the second quarter of the 10th century onwards there is a large difference between the actual calendar dates and those obtained by calibration using the valid calibration curve for the northern hemisphere. The relative differences between the radiocarbon ages, however, remain valid.